Popular Science Articles for Chemistry Teaching - Ketevan Kupatadze (Orbital: The Electronic Journal of Chemistry, 2017)
The presented paper reviews popular science articles (these articles are published in online magazine “The Teacher”) as one of the methods of chemistry teaching. It describes which didactic principles they are in line with and how this type of articles can be used in order to kindle the interest of pupils, students and generally, the readers of other specialties, in chemistry.  The articles review the main topics of inorganic/organic chemistry, biochemistry and ecological chemistry in a simple and entertaining manner. A part of the articles is about "household" chemistry. Chemical topics are related to poetry, literature, history of chemistry or simply, to fun news. The paper delineates the structure of popular science articles and the features of engaging students. It also reviews the teachers' and students' interview results about the usage of popular science articles in chemistry teaching process. The aforementioned pedagogical study revealed that the popular science articles contain useful information not only for the students of other specialties, but also for future biologists and ecologists (having chemistry as a mandatory subject at their universities). The articles are effectively used by teachers on chemistry lessons to kindle students' interest in this subject.DOI: http://dx.doi.org/10.17807/orbital.v9i3.960